SELAGINELLA ACTIVE FRACTIONS INDUCE APOPTOSIS ON T47D BREAST CANCER CELL - Handayani, Sri; Risdian, Chandra; Meiyanto, Edy; Udin, Zalinar; Andriyani, Rina; Angelina, Marissa (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
Apoptosis is an important target on anticancer mechanism. The purpose of this research is to investigate apoptosis induction of Selaginella plana Hieron active fractions on T47D cells. Absolute ethanol was used to extract Selaginella plana powders. Ethanolic extract was dilluted by methanol:water (4:1) and then fractionated by hexane (S_Hex), methylene chloride (S_MTC), ethyl acetate (S_EA), and buthanol (S_BuOH). The proliferation of T47D cell line was detected by SRB (Sulforhodamine B) assay which was measured at a wavelength of 515nm. Flowcytometry analysis to determine apoptosis was examined by Propidium Iodide (PI) and Annexin V assay using T47D breast cancer cell line. The result showed that the IC50 value of S_Hex, S_MTC, S_EA, and S_BuOH on T47D cells were 107 µg/mL, 4 µg/mL, 6 µg/mL, and 17 µg/mL respectively. The active fractions (S_MTC and S_EA) at its IC50 concentration significantly (P<0.05) increased the total number of early apoptotic cells in the T47D cells 3.39% and 4.1% respectively compared to that of control (1.95%). Based on the result, methylene chloride and ethyl acetate fraction of Selaginella plana induced apoptosis on T47D cell.Keywords: apoptosis, breast cancer, Selaginella